Aksi Prank dalam Perspektif Hadis: Analisis Teks, Konteks, dan Kontekstualisasinya - Rahmatullah Rahmatullah (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2021)
Abstract: This article departs from the problem of prank actions that often occur unethically in the public sphere. Hadith as arguments containing ethical norms is a relevant reference in addressing this matter. Therefore, this article aims to discuss the prank action from the perspective of the hadith and how the moral ideal of the hadith is implemented in carrying out prank actions. Referring to the hadith about joking and analyzed using Fazlur Rahman's double movement theory, this article sees that the legal status of prank action is situational. Prank actions can be done as long as they prioritize the principle of truth and do not have a negative impact on the surroundings, and vice versa. This is based on the editorial of the hadith which shows the Prophet's prohibition against taking something even though it meant jokes and jokes from the Prophet, which have never been separated from the truth. This hadith was motivated by the context of the Arab society at that time which was dominated by the situation of war and the process of internalizing Islamic teachings so that what the Prophet taught could not be separated from the interests of protection and education. Therefore, the moral ideal lies in an educational, preventive, and protective attitude. These moral ideals are principles that should be implemented in carrying out prank actions so that their actions become legitimate, do not cause negative impacts, and can generate positive responses in the public domain.